2020
DOI: 10.1111/1745-5871.12434
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise student migration: A trajectory analysis of Iranians moving from Turkey to Europe and North America

Abstract: In the last decade, political and economic constraints have prompted many students to leave Iran. While Europe and North America have traditionally been Iranians' preferred destinations, selective entry procedures make direct access increasingly difficult. This article focuses on Iranian students' stepwise migration strategies to reach Western countries through Turkey. My research indicates that stepwise migration theory can be applied to international students, as visa restrictions and the selectivity of West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
11
0
4
Order By: Relevance
“…Nowadays, contrary to the ancient history of migration, biological motivation (biological and finding food or shelter) is not as important as other factors. Another study (Zijlstra 2020) related to the Iranian immigrants showed the overwhelming majority of the Iranians intended to move stepwise from Turkey, in the course of 5-years to Europe. Although, attending different universities significantly affect the directions of their trajectories, overall (Zijlstra 2020), which is in line with our study that shows the interest of Iranian students to Europe.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, contrary to the ancient history of migration, biological motivation (biological and finding food or shelter) is not as important as other factors. Another study (Zijlstra 2020) related to the Iranian immigrants showed the overwhelming majority of the Iranians intended to move stepwise from Turkey, in the course of 5-years to Europe. Although, attending different universities significantly affect the directions of their trajectories, overall (Zijlstra 2020), which is in line with our study that shows the interest of Iranian students to Europe.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Another study (Zijlstra 2020) related to the Iranian immigrants showed the overwhelming majority of the Iranians intended to move stepwise from Turkey, in the course of 5-years to Europe. Although, attending different universities significantly affect the directions of their trajectories, overall (Zijlstra 2020), which is in line with our study that shows the interest of Iranian students to Europe. Ryazantsev, Afzali, and Rostovskaya (2020) revealed lack of facilities, political and economic relations are making talents, resources and human capitals to leave their home country.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu artışın önemli sebeplerinden biri olarak Amerika Birleşik Devletleri güdümlü İran'a yönelik ekonomik yaptırımlarına Ahmedinejat'ın 2005-2013 yılları arasındaki cumhurbaşkanlığında İran'ın nükleer programı konusunda izlemiş olduğu politikalara Birleşmiş Milletler ile Avrupa Birliği'nin de ekonomik yaptırımlar uygulaması olmuştur (Chaichian, 2012;Mehrabi, 2014). Bu yaptırımlar sonuç olarak İran ekonomisine ciddi olumsuz etkiler getirmiş ve toplumsal rahatsızlıkların artmasına neden olarak 2009 yılında başlayan Yeşil Hareket'e dönüşmüştür (Zijlstra, 2020). Ekonomik kriz İran'daki birçok sektörü etkilediği gibi eğitim alanını da etkilemiştir.…”
Section: Yükselen Trend: Uluslararası öğRenci Hareketliliğiunclassified
“…Çalışma, lisansüstü İranlı öğrencilerin, İran'a yönelik yaptırımların Avrupa ve Kuzey Amerika ülkelerine vize edinimlerinin zorlaştırması nedeniyle Türkiye'nin en-iyi ikinci seçenek olarak seçtiklerini vurgulamaktadır (Zijlstra, 2020). Yine aynı çalışma Pierre Bourdieu'nun sermaye biçimleri kategorileştirmesinden yararlanarak, bir taraftan Koç Üniversitesi gibi vakıf üniversitelerinde eğitim alan öğrencilerin aşamalı göç (stepwise migration) biçiminde Amerika Birleşik Devletleri, Kanada ve Avrupa ülkelerine geçiş için gereken sermayeleri Türkiye'de biriktirip, Türkiye'ye güzergahlarındaki basamak taşı olarak geldikleri ve bir üst derece eğitimleri için güzergahlarına devam ettiklerini göstermektedir (Zijlstra, 2020). Öte yandan devlet üniversitelerinde lisansüstü çalışmalarını sürdürenlerin ise edindikleri Türkiye'ye entegrasyonunu kolaylaştıran sermaye ile enine göç (crosswise migration) ile daha uzun süreler Türkiye'de kaldıklarını veya İran'a geri dönüş yaptıkları ayrımı bulgusuna ulaşmaktadır (Zijlstra, 2020).…”
Section: Yükselen Trend: Uluslararası öğRenci Hareketliliğiunclassified